A novel protocol for a "Citizen Panel" for diverse Public and Participant Involvement in the review and development of the process to access data in the UK Longitudinal Linkage Collaboration Trusted Research Environment - Garbovan, Lidis; Idemudia, Betty O.; Flaig, Robin; Campbell, Kirsteen; Evans, Katharine; Boyd, Andy; Cunningham-Burley, Sarah; Turner, Emma L. (International Journal of Population Data Science, 2025)
Background Researchers can apply to UK Longitudinal Linkage Collaboration (UK LLC) to access Longitudinal Population Study (LPS) data linked to health, non-health administrative and geo-environmental data. This paper describes the protocol for the "UK LLC Citizen Panel": a new method of incorporating a diverse public in decisions about the acceptability and suitability of the UK LLC data access process. The UK LLC Citizen Panel aims to embed public feedback and perceptions into UK LLC's data access process design and decision-making. Methods The UK LLC Citizen Panel will be created through a two-stage co-design process. Stage 1: UK LLC will identify and invite a public Steering Group to co-design the work of the Citizen Panel. The Steering Group will include public contributors from UK LLC's Public Involvement Programme and participant representatives from partner LPS. Stage 2: the UK LLC Citizen Panel will comprise participants of partner LPS and seldom-heard groups, primarily recruited via third sector organisations. The Panel will review the data access process during several online and in-person meetings. Findings will be analysed using thematic analysis and disseminated to UK LLC partner organisations, third sector organisations working with minority communities and young people under-represented in longitudinal studies, and networks of the Universities of Edinburgh and Bristol. Discussion The UK LLC Citizen Panel is a novel methodological approach that aims to consider a diverse public view of the use of a Trusted Research Environment to provide access to LPS data linked to health, non-health administrative and geo-environmental data. This diversity complements the existing public involvement in decision-making in all UK LLC data access and enables populations that are rarely heard in such decision-making to participate in and review the UK LLC data access process.